2002
DOI: 10.1007/s00228-002-0507-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of atorvastatin on erythrocyte membranes and serum lipids in patients with type-2 hypercholesterolemia

Abstract: . Our findings suggest that the atorvastatin therapy reverses the alteration of erythrocyte plasma membrane properties. It may improve blood rheology in patients with FH. This improvement in blood properties may contribute to the well-known beneficial effects of atorvastatin on cardiovascular risk in patients with severe hyperlipidemia and atherosclerotic vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…29 In humans, severe hypercholesterolemia is associated with alterations in RBC cholesterol and membrane fluidity, 30 which are improved by treatment with statins. 31 However, the majority of obese humans are not severely hypercholesterolemic, as was also the case in the present murine study. The diet we used in this study is rich in saturated fat and sucrose, leading to obesity and glucose intolerance, but the duration was not long enough to induce frank diabetes mellitus.…”
Section: Discussionsupporting
confidence: 74%
“…29 In humans, severe hypercholesterolemia is associated with alterations in RBC cholesterol and membrane fluidity, 30 which are improved by treatment with statins. 31 However, the majority of obese humans are not severely hypercholesterolemic, as was also the case in the present murine study. The diet we used in this study is rich in saturated fat and sucrose, leading to obesity and glucose intolerance, but the duration was not long enough to induce frank diabetes mellitus.…”
Section: Discussionsupporting
confidence: 74%
“…Deletion of ABCA7 cancels cholesterol-dependent regulation of phagocytosis but not cholesterol-independent one, indicating a specific contribution of ABCA7 to phagocytosis. Lowering cholesterol reportedly increases membrane fluidity and results in enhancement of phagocytosis [44, 45], so that ABCA7 may contribute to this process.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that de novo cholesterol synthesis is elevated in the lungs of Cftr -/- mice [3]. Evidence does suggest that membrane cholesterol content can be regulated by de novo synthesis [9,10]. Koter et al demonstrate that statin treatment reduces membrane cholesterol content in erythrocytes from 2.24 +/- 1.69 to 1.17 +/- 0.75 mg cholesterol/mg protein, a 47% reduction [9].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence does suggest that membrane cholesterol content can be regulated by de novo synthesis [9,10]. Koter et al demonstrate that statin treatment reduces membrane cholesterol content in erythrocytes from 2.24 +/- 1.69 to 1.17 +/- 0.75 mg cholesterol/mg protein, a 47% reduction [9]. It is possible that increased membrane cholesterol in CF plasma membrane is related to increased de novo cholesterol synthesis.…”
Section: Introductionmentioning
confidence: 99%